Effect Mechanism of the North Wind on Saltwater Intrusion in the Modaomen Channel - GAO Chenchen; CAI Duo (Renmin Zhujiang)
This paper establishes a three-dimensional mathematical salinity model for tide in the Modaomen Channel based on MIKE3 software, validates and calibrates the model by the measured data, conducts the numerical calculation of saltwater intrusion in the Modaomen Channel under north wind. and analyzes the effect of north wind on saltwater intrusion in the Modaomen Channel according to the simulation results and the theory of salt flux decomposition. The results show that the strength of north wind directly affect the salt transport pathway in Modaomen Channel. When the north wind is light, the salt above the branch port of the Modaomen Channel mainly comes from the Hengzhou Channel, and the Hongwan Channel serves for salt elimination by Main Modaomen Channel to other waters. However, under the action of strong north wind, the salt in the Modaomen Channel mainly comes from the Hongwan Channel.